Women Empowerment Fact, Stories and Programmes (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Women empowerment in India is a multifaceted issue that encompasses social, economic, political, and cultural dimensions. This review paper aims to explore the various aspects of women empowerment in India, examining the progress made, the challenges faced, and the strategies employed to promote gender equality. By reviewing existing literature, government policies, and non-governmental initiatives, this paper provides a comprehensive understanding of the state of women empowerment in India. The findings highlight significant strides in areas such as education and employment while also addressing persistent issues like gender-based violence and socio-cultural barriers.